2006
DOI: 10.1152/ajplung.00405.2005
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular heat shock protein 72 is a marker of the stress protein response in acute lung injury

Abstract: Previous studies have shown that heat shock protein 72 (Hsp72) is found in the extracellular space (eHsp72) and that eHsp72 has potent immunomodulatory effects. However, whether eHsp72 is present in the distal air spaces and whether eHsp72 could modulate removal of alveolar edema is unknown. The first objective was to determine whether Hsp72 is released within air spaces and whether Hsp72 levels in pulmonary edema fluid would correlate with the capacity of the alveolar epithelium to remove alveolar edema fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 46 publications
1
49
1
2
Order By: Relevance
“…3 Patients with hydrostatic pulmonary edema had Hsp72 levels of 160 Ϯ 51 ng/ml in the bronchoalveolar lavage fluid (BALF) vs 603 Ϯ 153 ng/ml in patients with ALI. Additionally, in this cohort, patients with impaired alveolar fluid clearance had lower levels of Hsp72 in the edema fluid (25). These results suggest that the presence of adequate levels of Hsp72 in the airways is associated with improved alveolar fluid clearance and may be protective in the setting of ALI.…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…3 Patients with hydrostatic pulmonary edema had Hsp72 levels of 160 Ϯ 51 ng/ml in the bronchoalveolar lavage fluid (BALF) vs 603 Ϯ 153 ng/ml in patients with ALI. Additionally, in this cohort, patients with impaired alveolar fluid clearance had lower levels of Hsp72 in the edema fluid (25). These results suggest that the presence of adequate levels of Hsp72 in the airways is associated with improved alveolar fluid clearance and may be protective in the setting of ALI.…”
mentioning
confidence: 56%
“…Other investigators have identified Hsp72 levels of 160 Ϯ 51 ng/ml in the BALF of patients with hydrostatic pulmonary edema vs 603 Ϯ 153 ng/ml in patients with ALI (25). Our initial mouse inhalation experiments were performed using 100 ng and 1 g of Hsp72 per inhalation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These could have accounted for the differential Hsp-72 expression noted in our study. Until recently, heat shock proteins were considered intracellular proteins, however, the detection of Hsp-60 and Hsp-72 in the sera of normal individuals (Pockley et al 1999;Pockley et al 2002) and observations of increased circulating levels of Hsp-72 in various conditions such as cardiovascular (Wright et al 2000;(Dybdahl et al 2005), acute lung injury (Ganter et al 2006), heat illness (Wu et al 2001), and trauma (Wright et al 2000;Wu et al 2001;Pittet et al 2002;Pockley et al 2002) raised the question of a potential extracellular role. In classical heatstroke, two clinical studies so far have reported high circulating levels of Hsp-72 and Hsp-60 with conflicting findings (Wang et al 2001;Huisse et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The heat shock proteins (Hsps) are a set of proteins synthesized in response to physical, chemical, or biological stresses, including heat exposure (McCormick et al, 2003;Ganter et al, 2006;Staib et al, 2007). Hsps are the most broadly distributed class of proteins and are also among the most highly conserved proteins in nature.…”
Section: Introductionmentioning
confidence: 99%